2013
DOI: 10.1016/j.hkjot.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Social Interaction and Atypical Sensory Processing in Children with Autism Spectrum Disorders*

Abstract: Objective/Background: Many children with autism spectrum disorders (ASDs) have sensory processing disorders (SPDs), which may limit many facets of daily life, including social interaction, an important domain of occupational therapy. Therefore, we examined the relationship between social interaction deficits and SPD in 4e6-year-old children with ASD without intellectual disorders. Methods: The Social Responsiveness Scale (SRS) and the Japanese Sensory Inventory-Revised (JSI-R) questionnaires were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 36 publications
(59 reference statements)
1
23
0
2
Order By: Relevance
“…In addition to the challenging sensory hypersensitivity/overload and hyposensitivity experienced by individuals with ASC, research has also linked sensory reactivity disorders to social communication difficulties ( 85 , 93 , 94 ). Fitzgibbon et al ( 95 ) proposed that both physical pain and social pain are processed atypically in individuals with ASC and insensitivity to pain, for example, could in turn limit empathy and understanding of pain in others.…”
Section: Impact Of Motor Coordination and Sensory Reactivity In Ascmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the challenging sensory hypersensitivity/overload and hyposensitivity experienced by individuals with ASC, research has also linked sensory reactivity disorders to social communication difficulties ( 85 , 93 , 94 ). Fitzgibbon et al ( 95 ) proposed that both physical pain and social pain are processed atypically in individuals with ASC and insensitivity to pain, for example, could in turn limit empathy and understanding of pain in others.…”
Section: Impact Of Motor Coordination and Sensory Reactivity In Ascmentioning
confidence: 99%
“…The evidence reviewed so far show that sensory and motor difficulties are prevalent in ASC and impact on social functioning ( 86 , 93 ). Evidence also suggests that these difficulties are present from birth, e.g., pre-social skill deficits ( 29 , 100 ), and increase the risk of developing ASC by aged 3 years ( 90 ).…”
Section: Sensorimotor Integration In Ascmentioning
confidence: 99%
“…Research has also identified links between sensory responsivity and the severity of ASC symptoms. For example, a number of studies have shown that sensory responsivity impairments impact social interaction and communication skills (Hilton et al, 2007 ; Reynolds et al, 2011 ; Matsushima and Kato, 2013 ). A more specific example is shown in research by Fitzgibbon et al ( 2013 ), who proposed that as physical and social pain appear to be processed differently in individuals with ASC, their insensitivity to pain could consequently limit the understanding and empathy for pain in others.…”
Section: Introductionmentioning
confidence: 99%
“…1 These atypical aspects of behavior may further interfere with the ability of children with ASD to engage with peers as they may appear inflexible or preoccupied. 20 Fluctuating states of regulation in reaction to sensory input may prevent children from orienting to and sustaining engagement in peer interaction. Even for children with ASD that have more advanced joint attention, play skills, and social orientation, peer interaction may still be significantly impacted by rigidity and adherence to their own plans.…”
Section: Restricted Interests and Repetitive Behaviorsmentioning
confidence: 99%